1999
DOI: 10.1002/(sici)1521-4141(199908)29:08<2539::aid-immu2539>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of ZAP-70 and inhibition of T cell activation by activated SHP1

Abstract: Studies with motheaten mice, which lack the SHP1 protein tyrosine phosphatase, indicate that this enzyme plays an important negative role in T cell antigen receptor (TCR) signaling. The physiological substrates for SHP1 in T lymphocytes, however, have remained unclear or controversial. To define these targets for SHP1 we have compared the effects of constitutively active and inactive mutants of SHP1 on TCR signaling. Expression of wild‐type SHP1 had a very small effect on the TCR‐induced tyrosine phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 68 publications
8
45
1
Order By: Relevance
“…In this respect, we have shown by cocapping experiments that CEACAM1 does indeed associate with the TCR complex, and that small amounts of ZAP-70 are coimmunoprecipitated with CEACAM1 from activated PBMCs. These results agree with studies by Mustelin and coworkers (33), who showed that SHP-1, but not SHP-2, can dephosphorylate ZAP-70 and inhibit T cell activation. In other studies, these investigators showed that SHP1 remains in the cytosol and requires activation for its inhibitory activity (32).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, we have shown by cocapping experiments that CEACAM1 does indeed associate with the TCR complex, and that small amounts of ZAP-70 are coimmunoprecipitated with CEACAM1 from activated PBMCs. These results agree with studies by Mustelin and coworkers (33), who showed that SHP-1, but not SHP-2, can dephosphorylate ZAP-70 and inhibit T cell activation. In other studies, these investigators showed that SHP1 remains in the cytosol and requires activation for its inhibitory activity (32).…”
Section: Discussionsupporting
confidence: 93%
“…Low levels of ZAP-70 were found associated with CEACAM1 before and after ligation with T84.1 with a 2-fold increase after ligation. The association of CEACAM1 with both SHP-1 and ZAP-70 is of special significance given that SHP-1-deficient mice have hyperactive TCR responses (30,31) and ZAP-70 has been shown to be a target of SHP-1 (32,33). The results for CaM were even more dramatic, with a 5-fold increase of binding after CEACAM1 ligation.…”
Section: Ceacam1 Associates With Shp-1 In Activated Pbmcsmentioning
confidence: 99%
“…The fact that bpV-mediated activation of COX-2 promoter was still detected in the CD45-negative cell line J45.01 is an indication that this T cell membrane PTP is not participating to this process (data not shown). The Src homology-containing PTP SHP-1 represents an ideal candidate, because it has been proposed as a negative regulator of T cell activation by decreasing the activity of several molecules involved in TCR signaling machinery, including p56 lck , phospholipase C␥, ZAP-70, and Syk (25,30,(53)(54)(55). Our data showing an inhibition of bpVinduced transcriptional activation when SHP-1 is overexpressed further strengthen this hypothesis.…”
Section: The Implication Of P36supporting
confidence: 75%
“…Human LYP, PTPH1, SHP1, LMPTP-B and HePTP cDNA in mammalian expression vector pEF5HA were described previously (Bottini et al, 2002;Brockdorff et al, 1999;Gjörloff-Wingren et al, 2000;Saxena et al, 1998;Vang et al, 2005). The HD-PTP cDNA was a gift from Dr. M. Ouchida (Okayama University, Japan; Toyooka et al, 2000) …”
Section: Expression Plasmidsmentioning
confidence: 99%